Taxonomic review of the genus Hydria Hübner, 1822 (Lepidoptera, Geometridae, Larentiinae) in the Middle East, with description of three new species and one new subspecies - Stadie, Dirk; Fiebig, Ralf; Rajaei, Hossein (Zootaxa, 2022)
The species of the genus Hydria in the Middle East are revised. The revision is based on morphological examination and genetic data (DNA-barcode). Additionally, information on the habitat preference, pre-imaginal stages and biology of the species are given as much as available. Three species (H. gernoti sp. n., H. schachti sp. n., H. loebeli sp. n.) and one subspecies (Hydria cervinalis taurica ssp. n.) are described as new to science. The taxonomic status of Hydria hyrcana (Staudinger, 1871) as bona species could be confirmed. The East African species, Hydria relicta (Herbulot. 1953) comb. n., is transferred from genus Rheumaptera to Hydria. Wing pattern and genitalia structures of all discussed species are illustrated.